The bicuspid aortic valve: Is it an immunological disease process?. Issue 6 (23rd April 2019) - Howard, Callum; Picca, Leonardo; Smith, Tristan; Sharif, Monira; Bashir, Mohamad; Harky, Amer
Abstract: Bicuspid aortic valves (BAVs) are the most common congenital cardiac condition and are characterized by a structural abnormality whereby the aortic valve is composed of two leaflets instead of being trileaflet. It is linked to an increased risk for a variety of complications of the aorta, many with an immunological pathogenesis. The aim of this study is to review and analyze the literature regarding immunological processes involving BAVs, associated common pathologies, and their incidence in the population. This study will also examine current trends in surgical and therapeutic approaches to treatment and discuss the future direction of BAV treatment.